Monkeypox Infection 2022: An Updated Narrative Review Focusing on the Neonatal and Pediatric Population - Francesca Gaeta; Francesco De Caro; Gianluigi Franci; Pasquale Pagliano; Pietro Vajro; Claudia Mandato (MDPI AG, 2022)
Monkeypox disease has been endemic in sub-Saharan Africa for decades, attracting remarkable attention only i23n 2022 through the occurrence of a multi-country outbreak. The latter has raised serious public health concerns and is considered a public health emergency by the World Health Organization. Although the disease is usually self-limiting, it can cause severe illness in individuals with compromised immune systems, in children, and/or the pregnant woman-fetus dyad. Patients generally present with fever, lymphadenopathy, and a vesicular rash suggestive of mild smallpox. Serious eye, lung and brain complications, and sepsis can occur. However, cases with subtler clinical presentations have been reported in the recent outbreak. A supportive care system is usually sufficient; otherwise, treatment options are needed in patients who are immunocompromised or with comorbidities. A replication-deficient modified and a live infectious vaccinia virus vaccine can be used both before and after exposure. Due to the persistent spread of monkeypox, it is necessary to focus on the pediatric population, pregnant women, and newborns, who represent fragile contagion groups. Here we assess and summarize the available up-to-date information, focusing on available therapeutic options, with insights into social and school management, breastfeeding, and prevention that will be useful for the scientific community and in particular neonatal and pediatric health professionals.